PENERAPAN STANDAR PELAYANAN PUBLIK MELALUI SARANA KOMUNIKASI DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MAMUJU - b, Amirullah B; Djabar, Sadly Abdul; Fitriana, Fitriana (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2024)
This study aims to determine and analyse the application of public service standards through communication facilities at the Population and Civil Registration Office of Mamuju Regency. This research was conducted at the Office of Population and Civil Registration of Mamuju Regency. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation. The results of this study indicate that the implementation of public service standards through communication facilities at the Population and Civil Registration Office of Mamuju Regency has not been maximised. The means of communication used consist of two means, namely electronic means in the form of a website: dukcapilmamuju.go.id and facebook dukcapil Mamuju and non-electronic means in the form of information boards displayed in the service room. On the website, information on the service standards for issuing ID cards in the form of requirements is different from the information on Facebook and also on the information board. In addition, the standard procedures in these three facilities were also found to be different. It was still found that the community as recipients of KTP issuance services had to wait more than the existing time standard. Meanwhile, the information on the standard cost of processing ID cards conveyed in the information facilities is in accordance with the services received by the community.